Kolaborasi Perpustakaan Umum dan TBM dalam Penyediaan Akses Koleksi Perpustakaan Bagi Masyarakat Daerah Terpencil - Kamilah Kinanti; Isti Sulastari; Sabrina Yulianti (Media Pustakawan, 2023)
Public libraries have a function to support the preservation of their respective regional cultural products and to facilitate the creation of a lifelong learning community. In practice, there are many obstacles faced by public libraries, one of which is access constraints. In addition to public libraries, the community is also obliged to support the availability of the library service facilities in their environment. In this research, Community Reading Garden/Taman Bacaan Masyarakat (TBM) represent the community as a supporting element in efforts to provide library access, especially for remote areas. The purpose of this research is to determine the efforts of the District Dispusip. X in providing access to library collections in remote areas, reveals the potential of TBM to support providing library access in remote areas, and the forms of collaboration expected by both parties. The research was carried out using a descriptive qualitative approach using interview data collection methods and case study observations at Dispusip District X and 5 TBMs in remote areas in District X, NTB Province. Based on the research, the results showed that TBM in X in providing library access in remote areas. The collaboration most expected by TBM is related to providing book collections.